Persepsi dan Penggunaan Buku Teks dan Sumber Belajar Online Mahasiswa Universitas Sulawesi Barat pada Mata Kuliah Fisika Dasar - Mutmainna Mutmainna; Musdar Musdar (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2022)
This research is done to (1) know the percentage of use of textbooks by students in the Basic Physics course; (2) to know the percentage of students using online learning resources in Basic Physics courses; (3) find out the tendency of students to use both learning sources while undergoing Basic Physics course activities in 2020/2021 even semester. This research is a quantitative descriptive study and applies incidental sampling. The population and sample are 259 and 50 students. The results showed that (1) the percentage of students using textbooks in the Basic Physics course was 54% stating often, 32% saying sometimes and 14% saying rarely; (2) the percentage of students using online learning resources in Basic Physics courses is 92% stating often, 6% stating sometimes, and 2% stating rarely; (3) the tendency of students to use both learning resources during their Even Semester 2020/2021 Basic Physics course shows that the use of online learning resources is greater than the use of textbooks.